5‐HT1B receptor imaging and cognition: A positron emission tomography study in control subjects and parkinson's disease patients. Issue 7 (25th May 2015) - Varrone, Andrea; Svenningsson, per; Marklund, Petter; Fatouros‐Bergman, Helena; Forsberg, Anton; Halldin, Christer; Nilsson, Lars‐Göran; Farde, Lars
ABSTRACT: Introduction: The serotonin 5‐HT1B receptor subtype is involved in the modulation of serotonin release and is a target of interest for neuroreceptor imaging. Previous studies have shown that the serotonin system is affected in Parkinson's disease (PD). Cognitive function, frequently impaired in PD, has been linked to the serotonin system. The aim of this study was to examine whether 5‐HT1B receptor availability in the brain of healthy subjects and PD patients is associated with measures of cognitive function. Methods: Twelve control subjects and ten PD patients with normal mini‐mental state examination scores were included in this study. Cognitive function was evaluated by assessment of semantic, episodic, and working memory, as well as fluency and visual attention. Creative ability, a measure of divergent thinking, was examined with the alternative uses of objects task. PET measurements were performed with the 5‐HT1B receptor‐radioligand [ 11 C]AZ10419369 using the HRRT system. Results: PD patients showed statistically significant lower measures of semantic and episodic memory, as well as creative ability, compared with control subjects. Statistically significant positive correlations were found in control subjects between creative ability and average 5‐HT1B receptor availability in grey matter, and in PD patients between scores of Beck Depression Inventory‐II and creative ability. Conclusion: Though creativity has been conventionally linked to dopamine function, our findings in control subjects suggest a link between 5‐HT1B receptor availability and creative ability. In PD patients, creative ability was significantly associated with depressive symptoms but not with 5‐HT1B receptor availability. This finding deserves further investigation in future studies.Synapse 69:365–374, 2015. © 2015 Wiley Periodicals, Inc. Abstract : Using positron emission tomography with the 5‐HT1B receptor radioligand [ 11 C]AZ10419369, the authors show in control subjects a positive correlation between 5‐HT1B receptor availability in the average grey matter and creative ability. This study is the first to show a relationship between creative ability and serotonin function.